Linear motor driven-rotary motion of a membrane-permeabilized ghost in Mycoplasma mobile - Kinosita, Yoshiaki (Sci Rep, 2018)
Mycoplasma mobile exhibits a smooth gliding movement as does its membrane-permeabilized ghost model. Ghost experiments revealed that the energy source for M. mobile motility is adenosine triphosphate (ATP) and that the gliding comprises repetitions of 70 nm steps. Here we show a new motility mode, in which the ghost model prepared with 0.013% Triton X-100 exhibits directed rotational motions with an average speed of approximately 2.1 Hz when ATP concentration is greater than 3.0 × 10(−1) mM. We found that rotary ghosts treated with sialyllactose, the binding target for leg proteins, were stopped. Although the origin of the rotation has not been conclusively determined, this result suggested that biomolecules embedded on the cell membrane nonspecifically attach to the glass and work as a fluid pivot point and that the linear motion of the leg is a driving force for the rotary motion. This simple geometry exemplifies the new motility mode, by which the movement of a linear motor is efficiently converted to a constant rotation of the object on a micrometer scale.